The cat, a hidden pet in Mesopotamia? Tablet 45 of Šhumma alu and a method to identify this feline - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
Unlike Egypt, where the cat played an important role, Mesopotamia offers very limited documentation on cats, both in textual and archaeological data. This article aims to bring together the different pieces of a puzzle that is difficult to restore and to question the reasons for this limited documentation.